Keefektifan Konseling Kelompok Cognitive Behavioral dengan Teknik Self-Talk untuk Mengurangi Kecemasan Mahasiswa Semester Akhir dalam Penyelesaian Skripsi - Savitri, Lia Luthfi; Ramli, M; Multisari, Widya (citeus, 2025)
This study aimed to determine the effectiveness of cognitive behavioral group counseling with self-talk techniques to reduce anxiety in final-semester students. This research is included in quantitative research with experimental methods, and the research design used is one group pretest and posttest design. The research population is 2018 class students at Universitas Negeri Malang who are completing their thesis. We are taking research subjects using a purposive sampling technique. The subjects in this study were five students with high anxiety levels. Cognitive behavioral group counseling with self-talk techniques was carried out in seven sessions: one pre-counseling session, five counseling sessions, and one post-counseling session. We developed an anxiety scale instrument based on Nolen's theory. Based on the pretest and posttest results, it is known that cognitive-behavioral group counseling with self-talk techniques effectively reduces final semester student anxiety in completing thesis.